THE EFFECT OF SELF-REWARD CONTENT ON CONSUMPTIVE BEHAVIOR WITH SELF-CONTROL AS A MEDIATING VARIABLE - Sri Wahyuning Astuti; Nabila, Isnaini Amirotu (International Journal of Cultural and Social Science, 2025)
This study aims to examine the influence of self-reward content on consumptive behavior, with self-control as a mediating variable. A quantitative approach was employed using a survey method involving 400 Generation Z respondents in Indonesia who actively use TikTok and have encountered self-reward-themed content. Data were collected through an online questionnaire and analyzed using t-test, ANOVA, F-test, and path analysis to examine both direct and indirect relationships among variables. The results show that self-reward content has a significant positive effect on consumptive behavior (t = 52.939, p < 0.05) and also a significant positive effect on self-control (t = 6.373, p < 0.05). Meanwhile, self-control has a significant negative effect on consumptive behavior (t = -2.872, p < 0.05) and is proven to mediate the relationship between self-reward content and consumptive behavior based on the path analysis results (p = 0.009). These findings indicate that although self-reward content encourages consumptive behavior, strong self-control can mitigate its impact. This study offers new insights into the dynamics of digital consumptive behavior among Generation Z in today’s social media landscape.